2005
DOI: 10.1111/j.1523-1739.2005.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Wolf Translocation as a Nonlethal Method to Reduce Livestock Conflicts in the Northwestern United States

Abstract: Successful nonlethal management of livestock predation is important for conserving rare or endangered carnivores. In the northwestern United States, wolves (Canis lupus) have been translocated away from livestock to mitigate conflicts while promoting wolf restoration. We assessed predation on livestock, pack establishment, survival, and homing behavior of 88 translocated wolves with radiotelemetry to determine the effectiveness of translocation in our region and consider how it may be improved. More than one-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 24 publications
1
75
1
3
Order By: Relevance
“…It has been shown that urban raccoons excluded from breeding dens usually make new dens in nearby man-made structures (O'Donnell and DeNicola 2006). Similarly, carnivores translocated from an area where they have been responsible for livestock predation or other damage problems frequently return to the original area or exhibit similar nuisance behaviour elsewhere (Linnell et al 1997;Bradley et al 2005). Hence, it is important to gather objective evidence on the effectiveness of management strategies in order to avoid potentially damaging and costly outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that urban raccoons excluded from breeding dens usually make new dens in nearby man-made structures (O'Donnell and DeNicola 2006). Similarly, carnivores translocated from an area where they have been responsible for livestock predation or other damage problems frequently return to the original area or exhibit similar nuisance behaviour elsewhere (Linnell et al 1997;Bradley et al 2005). Hence, it is important to gather objective evidence on the effectiveness of management strategies in order to avoid potentially damaging and costly outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Where the ethics of culling native predators are questioned (Witmer et al 2000;Ziegltrum 2008), translocation is often considered a humane alternative (Massei et al 2011). Translocation, however, may incur significantly higher costs than culling (Sillero-Zubiri et al 2010) and benefits to prey populations may not be sustained, with the movement of translocated predators back into the area a recurring problem (Bradley et al 2005;Linnell et al 1997). The welfare of translocated animals must also be considered, as translocation programmes often result in high levels stress and mortality in the target individuals (Teixeira et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…N055's premature age probably contributed to this success, as young brown hyaenas usually display submissive behaviours during intraspecific encounters (Mills, 1981;Mills, 1983b), immigrate or become nomadic (Mills, 1982). The animal's extensive and immediate exploratory movements are consistent with post-release behaviour of other large carnivores (see Bradley et al, 2005;Houser et al, 2011;Priatna, Santosal, Prasetyo & Kartono, 2012;Riley, Aune, Mace & Madel, 1994;Ruth, Logan, Sweanor, Hornocker & Temple, 1998;Weilenmann et al, 2010). The hyaena left the target release area and died less than six months post-release, therefore failing to achieve true translocation success.…”
Section: Resultsmentioning
confidence: 90%